Name changes for chinese Pilea (Urticaceae) / C. J. Chen (Chen Jia-rui); A. K. Monro; L. Chen - Chen, Chia - Jui; Monro, Alex K.; Chen, Lian (2007)
Two new names in Pilea Lindley from China are published: Pilea panzhihuaensis C. J. Chen, A. K. Monro & L. Chen and P. spicata C. J. Chen & A. K. Monro. A lectotype is designated for the basionym of P. spicata, Smithiella myriantha Dunn. The origins of the new names are explained, synonymy of the resurrected name is given, and an illustration of P. panzhihuaensis is provided.
il.
Keywords: Flora; China; Urticaceae; Pilea; Podophyllum